2019
DOI: 10.2298/mpns1902030k
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic symptoms in Parkinson’s disease: Etiology, prevalence and treatment

Abstract: Introduction. Parkinson's disease is the second most common neurodegenerative disease with as many as 50-70% of patients experiencing psychotic symptoms during the course of the illness. Our aim was to provide an evidence-based review on the etiology, prevalence and management of psychotic symptoms in Parkinson's disease. Material and Methods. We used references from the "Medline" database published from 1999 to 2019. Results. The most common psychotic symptoms in Parkinson's disease are visual hallucinations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It was previously thought that the affectation of sounds in PD depends on the place of articulation. For example, according to Logeman, as cited in Read et al [5] the disease primarily affects posterior sounds and then those sounds whose articulation takes place in the anterior parts of the oral cavity. In their empirical study, Read et al [5] concluded that the limitation of oral musculature mobility in PD affects all sounds of spoken language equally and simultaneously.…”
Section: Articulation Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…It was previously thought that the affectation of sounds in PD depends on the place of articulation. For example, according to Logeman, as cited in Read et al [5] the disease primarily affects posterior sounds and then those sounds whose articulation takes place in the anterior parts of the oral cavity. In their empirical study, Read et al [5] concluded that the limitation of oral musculature mobility in PD affects all sounds of spoken language equally and simultaneously.…”
Section: Articulation Disordersmentioning
confidence: 99%
“…For example, according to Logeman, as cited in Read et al [5] the disease primarily affects posterior sounds and then those sounds whose articulation takes place in the anterior parts of the oral cavity. In their empirical study, Read et al [5] concluded that the limitation of oral musculature mobility in PD affects all sounds of spoken language equally and simultaneously. The disorders are most noticeable during the production of sounds that require a wide jaw angle for articulation (such as sounds A, O, L, R, K, and G) and those that require the engagement of different groups of articulatory muscles [18].…”
Section: Articulation Disordersmentioning
confidence: 99%
See 1 more Smart Citation